Impact of balanced scorecard on managerial performance: mediating effects of role clarity - Shazrul Ekhmar Abdul Razak,; Mazlina Mustapha, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Performance of hotel operational managers is crucial in delivering quality service to customers. Prior studies claimed that balanced scorecard (BSC) measures can clarify managers’ roles to improve their performance. Thus, this study examines the relationship between the BSC measure, role clarity, and managerial performance in the Malaysian hotel sector. This study also investigates the mediating effect of role clarity between the BSC measures and managerial performance. 475 questionnaires were distributed to managers of 3-, 4-, and 5-star hotels in Malaysia. Analysis from Structural Equation Modelling (SEM) found a significant relationship between the BSC measures and role clarity. Role clarity has a significant impact on managerial performance. The results also found that role clarity partially mediates the relationship between the BSC measures and managerial performance. These results provide information to policymakers on the importance of BSC measures to stimulate positive behaviour through role clarity for managers to deliver quality service.